A cross-sectional study of early language abilities in children with sex chromosome trisomy (XXY, XXX, XYY) aged 1–6 years. Issue 2 (17th February 2022) - Urbanus, Evelien; Swaab, Hanna; Tartaglia, Nicole; Boada, Richard; van Rijn, Sophie
ABSTRACT: Children with sex chromosome trisomy (SCT) are at increased risk for developing language difficulties. Earlier studies have reported that as many as 70–80% of individuals with SCT show some form of language difficulties. Language develops rapidly in the first years of life; knowledge about language development at an early age is needed. The present study aims to identify the language abilities of young children with SCT across multiple language domains and to identify the percentage of children that, according to clinical guidelines, have language difficulties. Children between the ages of 1–6-years ( N SCT  = 103, N controls  = 102) were included. Nonverbal communication, early vocabulary, semantic, syntax, and phonological skills were assessed. Language difficulties were already present in 1-year-old children with SCT and across the age range in various language domains. Clinical classification showed that, depending on the assessed domain, 14.8–50.0% of the children scored below the 16 th percentile. There was no effect of time of diagnosis, ascertainment bias, research site, nor SCT specific karyotype (XXX, XXY, XYY) on language outcomes. Overall, language difficulties can already be present in very young children with SCT within various language domains. These findings appear to be robust within the SCT group. These results highlight the importance of monitoring both receptive and expressive language development already at the earliest stages of nonverbal communication. Finally, as early language skills are the building blocks for later social communication, literacy, and self-expression, studies that investigate the effect of early interventions on later language outcomes are warranted.